2013
DOI: 10.1007/s12029-013-9546-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutational and Clinical Predictors of Pathologic Complete Response in the Treatment of Locally Advanced Rectal Cancer

Abstract: Purpose Preoperative chemoradiation (CRT) for locally advanced rectal adenocarcinoma achieves pathologic complete response (pCR) in 8–20 % of patients. Mutations in critical cancer genes may contribute to lack of pCR. We retrospectively evaluated our institutional experience to determine potential mutational and clinical predictors of pCR in patients treated with CRT. Methods Patients with locally advanced rectal adenocarcinoma treated with preoperative CRT (n = 79) were identified. A clinical cancer genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 20 publications
2
25
0
Order By: Relevance
“…23 However, the impact of BRAF mutational status on response to preoperative chemoradiation is still controversial, with some studies showing low pathological complete response rates in RAS-or BRAFmutated tumors 6,7 and others no impact 8,9 and this is likely due to the small number of BRAF-mutated rectal carcinomas in these clinical series. In such a context, the question whether BRAF oncogenic mutations enhance the apoptotic threshold of rectal cancer cells and impact on response to radiation is extremely relevant, since it is established that human BRAF V600E CRCs are resistant to apoptosis and poorly responsive to standard chemotherapeutics and molecular targeted agents.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…23 However, the impact of BRAF mutational status on response to preoperative chemoradiation is still controversial, with some studies showing low pathological complete response rates in RAS-or BRAFmutated tumors 6,7 and others no impact 8,9 and this is likely due to the small number of BRAF-mutated rectal carcinomas in these clinical series. In such a context, the question whether BRAF oncogenic mutations enhance the apoptotic threshold of rectal cancer cells and impact on response to radiation is extremely relevant, since it is established that human BRAF V600E CRCs are resistant to apoptosis and poorly responsive to standard chemotherapeutics and molecular targeted agents.…”
Section: Discussionmentioning
confidence: 98%
“…5 By contrast, conflicting results have been proposed on the role of BRAF mutations in driving the sensitivity of rectal carcinoma cells to radiation, with some studies showing poor responses and others no influence. [6][7][8][9] Thus, this study was designed to evaluate in vitro the radiosensitivity of CRC cells with different RAS/BRAF mutational profiles and exploit cyclin-dependent kinase 1 (CDK1) targeting as a strategy to improve efficacy of radiation therapy in BRAF V600E tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…This variation could be ascribed to the use of different methodologies. Some studies also examined genetic/epigenetic changes or protein expression levels, although research is still at an early stage. Nevertheless, large‐scale validation studies of predictive markers are necessary before incorporating such methodologies into future clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although RT activates RAS‐MAPK signaling in KRAS‐mutant cells, inhibition of MAPK signaling by mitogen‐activated protein extracellular signal‐regulated kinase (MEK) inhibition can attenuate survival after RT . Emerging clinical evidence also supports the finding of relative RT resistance in tumors that harbor KRAS mutations . Trametinib, a potent and selective MEK1/MEK2 inhibitor that is FDA approved for metastatic or unresectable, BRAF V600E/V600K‐mutant melanoma, has been shown to have antiproliferative activity in human KRAS‐mutant or BRAF‐mutant CRC cell lines with reductions in extracellular signal‐regulated kinase (ERK) activation .…”
Section: Rationale For Radiation‐targeted Therapy Combinationsmentioning
confidence: 96%
“…[25][26][27] Emerging clinical evidence also supports the finding of relative RT resistance in tumors that harbor KRAS mutations. 19,[28][29][30][31] Trametinib, a potent and selective MEK1/MEK2 inhibitor that is FDA approved for metastatic or unresectable, BRAF V600E/V600K-mutant melanoma, has been shown to have antiproliferative activity in human KRAS-mutant or BRAF-mutant CRC cell lines with reductions in extracellular signalregulated kinase (ERK) activation. 32 Multiple groups have shown that MEK1/MEK2 inhibitors in RASmutant carcinoma preclinical models result in effective radiosensitization (with or without the additive effects of 5-FU), resulting in tumor cell death and tumor growth delay through increased apoptosis, DNA damage-induced cell death, reduced DNA repair, and a reduction in hypoxic response.…”
Section: Mitogen-activated Protein Extracellular Signal-regulated Kinmentioning
confidence: 99%